Twenty-First Meeting of the National Development Council Summary Record - Planning Commission (Planning Commission, 1964)
The National Development Council, at its last meeting held on October 27 and 28, 1964, set up five Committees on (1)Agriculture and Irrigation, (2) Industry, Power and Transport, (3) Social Services, (4) Development of Hill Areas, and (5) Resources to go into and evolve desirable guide-lines for development and planning in the respective sectors for the Fourth Plan.
Government of India Planning Commission
Government of India Planning Commission